Asymptomatic Hyperuricemia and the Kidney: Lessons from the URRAH Study - Cecilia Barnini; Elisa Russo; Giovanna Leoncini; Maria Carla Ghinatti; Lucia Macciò; Michela Piaggio; Francesca Viazzi; Roberto Pontremoli (Metabolites)
Chronic kidney disease (CKD) is a prevalent global health concern affecting approximately 850 million people worldwide, with a significant and rising mortality rate. CKD often coexists with hyperuricemia (HSUA), which is also increasingly common due to its association with hypertension, obesity, and diabetes. The interplay between hyperuricemia and CKD is complex; while in vitro studies and animal models support a role for uric acid mediating glomerular and tubule-interstitial damage, and HSUA has been shown to predict the onset and progression of CKD, the expectations of renal protection by the use of urate lowering treatment (ULT) are inconsistent. A significant challenge in managing asymptomatic HSUA in CKD patients lies in determining the appropriate SUA threshold values. Recent research, including the URRAH project, has sought to identify SUA cut-offs predictive of cardiovascular mortality, but these thresholds may vary depending on the severity of CKD. This variability complicates the establishment of universal guidelines for treating asymptomatic HSUA, leading to a lack of specific recommendations in clinical practice. In conclusion, while hyperuricemia is recognized as a prognostic factor for CKD and cardiovascular risk, more research is needed to refine the threshold values for SUA and to identify which patients may benefit from ULT. Stratification based on glomerular filtration rate may be necessary to tailor the treatments and improve outcomes in this population.